Case report: Donor lymphocyte infusion and blinatumomab as treatment for acute lymphoblastic leukemia relapse after allogeneic hematopoietic stem cell transplantation - Antonucci, Flavia; Marotta, Serena; Celentano, Maria; Pedata, Mariangela; Riccardi, Cira; Luise, Cristina; Carobene, Angela; Muggianu, Simona Maria; Viola, Assunta; Caputo, Mafalda; Leone, Stefania; Migliaccio, Ilaria; et al. (Frontiers in Hematology, 2024)
To date, the effect of blinatumomab and donor lymphocyte infusion association as a salvage treatment for acute lymphoblastic leukemia (ALL) relapse after allogeneic transplant procedure is still unknown. Here, we report a case report of a patient with early relapse of ALL after allogeneic hematopoietic stem cell transplant successfully treated with a combination of blinatumomab and DLI.